Synthesis of pyrene and benzo[alpha]pyrene adducts at the exocyclic amino groups of 2 '-deoxyadenosine and 2'-deoxyguanosine by a palladium-mediated C-N bond-formation strategy - Lakshman, MK; Ngassa, FN; Bae, S; Buchanan, DG; Hahn, HG; Mah, H (AMER CHEMICAL SOC, 2003)
Single-electron oxidation of the carcinogenic hydrocarbon benzo [alpha] pyrene (BalphaP) is thought to result in a radical cation intermediate and this species has been proposed to cause alkylation at the nitrogens of the purine nucleobases. Although several different nucleoside adducts have been isolated as arising from this mode of metabolic activation, there are no selective, total syntheses of the stable exocyclic amino group adducts formed by the single-electron oxidation of any hydrocarbon with the purine 2'-deoxynucleosides to date. In this paper we disclose the synthesis of the model adducts N-6-(1-pyrenyl)-2'-deoxyadenosine and N-2-(1-pyrenyl)-2'-deoxyguanosine as well as the first synthesis of the carcinogen-linked nucleoside derivatives N-6-(6-benzo [a] pyrenyl)-2'-deoxyadenosine and N-2-(6-benzo[a]pyrenyl)-2'-deoxyguanosine via a palladium-mediated C-N bond formation. Two different coupling strategies were attempted: coupling of an aryl bromide with a suitably protected nucleoside and the coupling of an arylamine with a suitable halonucleoside. The former had somewhat limited applicability in that only N6-(I-pyrenyl)-2'-deoxyadenosine was prepared by this method; on the other hand, the latter was more general. However, there are noteworthy differences in the amination reactions at the C-6 and C-2 positions. Reactions at the C-6 resulted in the competing formation of a 1:2 amine-nucleoside adduct in addition to the desired monoaryl nucleoside. Such a dimer formation was not observed at the C-2. The C-2 adducts, however, displayed an interesting conformational behavior.
Keywords: POLYCYCLIC AROMATIC-HYDROCARBONS; SITE-SPECIFIC INCORPORATION; HIGHLY EFFICIENT SYNTHESIS; REGION DIOL EPOXIDE; ARYL HALIDES; CATALYZED AMINATION; CHEMICAL-SYNTHESIS; DNA-ADDUCTS; MOUSE SKIN; POSTOLIGOMERIZATION SYNTHESIS